Persistent symptoms, exacerbations and drug side effects despite treatment in myasthenia gravis - Reyes‐Leiva, David; Carbayo, Álvaro; Vesperinas‐Castro, Ana; Rojas‐García, Ricard; Querol, Luis; Turon‐Sans, Janina; Pla‐Junca, Francesc; Olivé, Montse; Gallardo, Eduard; Pujades‐Rodriguez, Mar; Cortés‐Vicente, Elena (European journal of neurology, 2025)
Background Generalized myasthenia gravis (gMG) is characterized by fluctuating muscle weakness. Exacerbation frequency, adverse events (AEs) related to immunosuppressant therapy and healthcare resource utilization (HCRU) are not well understood. Our study aimed to describe long‐term clinical outcomes, drug‐related AEs and estimated HCRU in gMG patients. Methods This was a retrospective cohort analysis of clinical data from patients with gMG followed‐up over eight consecutive years in a Spanish referral unit. Myasthenia Gravis Foundation of America (MGFA) clinical classification, MGFA post‐interventional status (MGFA‐PIS), Myasthenia Gravis Activities of Daily Living (MG‐ADL) score, exacerbations, MG crises, therapies, AEs reported, specialist consultations and emergency room visits were studied biannually. An estimation of HRCU was made based on these data. Results Some 220 patients newly diagnosed with gMG were included. Ninety percent were seropositive (84.5% anti‐acetylcholine receptor [AChR], 5.9% anti‐muscle‐specific kinase [MuSK]). Baseline mean MG‐ADL score was 5.04 points (SD 3.17), improving to 0.7 points (SD 1.40) after 8 years. Exacerbations were more frequent in years 1–2 (30.1%) but still occurred in years 7–8 (20.2%). Myasthenic crisis frequency remained 1% in years 7–8. Eighty‐nine percent achieved MGFA‐PIS minimal manifestations or better at 8 years. Fifty‐one percent of patients reported at least one AE during the study period, leading to drug withdrawal in approximately 20% of cases. HCRU decreased between years 1–2 to years 7–8 with an estimated cost of MG from 8074.19 € per patient/year to 1679.46 €, respectively. Conclusions There is a group of MG patients that suffers from persistent symptoms and exacerbations (11%–20%) or MG crises, and drug AEs, which may increase disease burden and impact on the healthcare system.